IKLIM ETIKA, ETHICAL BEHAVIOR PLANNED DAN KINERJA BERKELANJUTAN - Erna Kusumawati (LPPM Nusa Mandiri, 2017)
Discussion about moral standards and assessment related to the implementation of the functions of the lecturers still rarely performed. The discourse is limited more to discuss how the output of the function of a lecturer in a college. The research objective was to obtain an overview and analyze Climate ethics, Ethical Behavior planned and Sustainable Performance Orientation. The research method using descriptive verification by the survey. The results showed that the action is not yet fully based on the basic moral principles in the context of HRM as a means of orientation behavior. Ethical Behavior planned limited to the cognitive dimension. The affective dimension and the behavior was confined mainly to the application of the values of authentic and willingness responsible for developing research results. Continuous performance orientation is limited to consideration of individual benefits.